THE DETERMINANT OF OUTPATIENT HEALTH SERVICES UTILIZATION FOR ELDERLY PATIENT IN INDONESIA (SUSENAS 2017 DATA ANALYSIS) - Putri, Rizki Asriani; Ilyas, Yaslis (UI Scholars Hub, 2019)
Indonesia has entered an aging population as showed by the number of elderly population which has reached more than 7% of the population. Basically, the increase in the elderly population will also increase the number of illnesses, because the more a person ages, the physical condition will decrease and be more susceptible to disease. This research is a quantitative study that aims to determine the determinants of outpatient health service use for Indonesian elderly in 2017. This research used secondary data from the 2017 National Socio-Economic Survey (Susenas) results with the unit of analysis is people aged ≥ 60 years who had health complaints. The analytical method used is logit regression analysis. The results showed that gender, education, employment status, residential area, health insurance ownership, economic status, and disruption of activity due to illness had a p-value of 0,000 < 0,05 which meansthat it was significantly associated with the utilization of outpatient health services. The most dominant variable is the disruption of activity due to illness. The government can issue policies related to efforts to register each elderly person into health insurance through optimizing a healthy Indonesian program with a family approach. The government is expected to be more assertive in monitoring and evaluating elderly health services by considering factors that support the elderly in utilizing health services to achieve healthy aging and active aging.